Exploring the relationship between extracurricular activities and stress levels among university students: A cross-sectional study - Mona Zeidan; Rouba Ballout; Nayla Al-Akl; Samer A. Kharroubi (PLoS ONE, 2025)
Background Extracurricular activities (ECA) offer students valuable opportunities to engage in nonacademic pursuits, which can be a powerful strategy for managing stress and achieving a balanced life. The present study aimed to assess the prevalence of stress among students from the American University of Beirut (AUB), and examine the association between ECA and stress levels. Methods A cross-sectional, self-administered online survey was conducted among AUB students in Lebanon during the spring 2024 semester. Stress levels were evaluated using Cohen’s Perceived Stress Scale (PSS), a validated screening tool. The questionnaire also included general questions about students’ participation in ECA. Multinomial logistic regression analysis was applied to explore the association between ECA and stress levels, and to investigate which socio-demographic characteristics are associated with stress levels. Results A total of 365 students completed the questionnaire. Findings showed that 71.5% of students experienced symptoms of moderate stress and 38.6% of the participants reported being involved in ECA at AUB. Our results indicated a significant association between perceived stress and participation in ECA. Students who did not participate in ECA had higher odds of experiencing stress compared to those who did (OR= 2.628, p = 0.031). Additionally, the models identified three more correlates of stress. Male students had lower odds of experiencing moderate stress than female students (OR=0.371, p = 0.008). Students who studied 10–15 hours per week had higher odds of experiencing moderate stress compared to those who studied 15 or more hours per week (OR=3.157, p = 0.043). Finally, unemployed students had higher odds of experiencing high stress compared to employed students (OR= 5.191, p < 0.001). Conclusions This study revealed alarming stress levels among university students in Lebanon. The findings suggest that encouraging ECA participation is essential for enhancing student well-being.